The efficacy of miswak (Kayu sugi) containing toothpaste on dental plaque accumulation - Rusminah, Nunung; Pribadi, Indra Mustika Setia; Thillainathan, Komala (Universitas Padjadjaran, 2018)
Introduction: Salvadora persica, also known as miswak (Kayu sugi), has been used as natural toothbrushing compound for centuries. Many research suggested that it contains medically beneficial properties such as abrasives, antiseptics, astringent, detergent, enzyme inhibitors, and fluoride. The objective of this study was to assess the efficacy of miswak containing toothpaste on dental plaque accumulation. Methods: The total of 30 subjects consisted of male students of Bandung Institute of Technology, aged between 18 – 26 years old. The plaque value was measured using the Turesky Gilmore & Glickman Index Modification of Quigley & Hein at baseline (day 0), day 1, day 3, and day 7. Commercial toothpaste (Pepsodent®) was used as the control group in this pre and post-test designed, single-blind study. Results: After analysed using the paired t-test, the data showed that the mean plaque index of respondents using miswak and non-miswak containing toothpaste from baseline until day 7, were 1.70/1.19 and 1.61/1.44 respectively (p < 0.05). The mean plaque index reduction of respondents using miswak and non-miswak containing toothpaste from baseline until day 7, were 0.39 and 0.25 respectively (p = 0.00). Conclusion: Both kinds of toothpaste were able to reduce plaque, but miswak containing toothpaste was found to be more effective in reducing dental plaque accumulation.